Development of stem-based lkpd on the theme of my house's electric circuits to improve explanation, inference and evaluation skills - Kiswari, Lusinta; Singgih, Suwito; Muhlisin, Ahmad (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2023)
This study aims to produce a valid, practical, and effective STEM-based LKPD product to improve students' explanatory, inference, and evaluation skills. The method used in this study is the research and development method. A validity test has been carried out consisting of a product validity test that is declared valid and suitable for use with a percentage of 80.9%. The effectiveness test is carried out with n-gain and effect size tests. Each obtained a result of 0.68 with the medium category and 2.7 with the high category. Practicality tests conducted by teachers obtained an average result of 83% and students of 87%. So, STEM-based LKPD can effectively improve students' explanatory, inference, and evaluation skills.